IMPLEMENTATION OF GLOBAL COMPETENCY IN HIGHER EDUCATION - T. A. Anoshkova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2015)
The article is devoted to the thorough characteristics of global competence as an important component of training young specialists. Globalization processes led to the irreversible changes in the modern society, opening the world borders and increasing the role of international communication. Such processes affected the higher education of numerous countries and created the concept of global education. The article describes global competency as the essential component of global education. There are several definitions of global competency, given by American, European and native scientists. The key competencies are determined on the basis of the research works of the scientists. The author gives general characteristic of these competencies in accordance with the emphasized approaches. The emphasis is placed on the understanding of cultural differences and intercultural communication with the leading role of foreign language in global education process. In the current article it is explained the connection between competencies acquired by students at the universities and the demands of the real-world labor market. The article also underlines the dominant position of a teacher in the successful acquirement of global competency by the students. It gives the examples of the pedagogical skills necessary for developing competencies in the context of global education.